SPOTLIGHT @LG240: Poets & Patriots: Merdeka Poetry Challenge - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
The Young Scriptors Club (YSC), under the Applied Language Society (APPLES), organised a programme called Poets & Patriots: Merdeka Poetry Challenge which lasted for 18 days and culminated on 20th August 2022. In conjunction with the independence month, patriotism was chosen as the theme of this poetry-writing programme. The main goal of this programme was to appreciate and polish the talents of young students in poetry writing. The submitted poems were evaluated by the three judges from Akademi Pengajian Bahasa. The judges were Zaamah Mohd Nor, Mazura Anuar, and Midiyana Mohamad.